Investigation on the Distribution of Antibiotic Resistant Bacteria In Dry Fish of Chalan Beel Area From Northwestern Part of Bangladesh - Zohura, Fatema; Rahman, M Habibur (Journal of Bio-Science, 2024)
Dried fish, a valuable animal protein source, may pose health risks due to microbial contamination influenced by water quality, hygiene practices, handling, packaging, and transportation. This research focuses on conducting an in-depth analysis of the occurrence and antibiotic resistance patterns of bacteria, identified through 16S rRNA sequencing, in different dried fish varieties obtained from the Chalan beel area in Northwestern Bangladesh. For the purpose of this study, homogenization of collected samples was carried out and resulting homogenates were refrigerated at a temperature of -20°C. Then the samples were subjected to a series of 10-fold dilutions and spread over 1.5% nutrient agar supplemented with Tetracycline. Thereafter, plates were incubated at 37°C for a duration of 24 hours to form bacterial colonies. Twelve aseptically collected dried fish samples had a total viable count ranging from 2.0 × 10² to 6.5 × 10⁵ CFU/ml, with tetracycline influence at 32 µg/ml (7 × 10² to 5.4 × 10³ CFU/ml) and 64 µg/ml (3.0 × 10² to 2.1 × 10³ CFU/ml). Notably, Tengra fish (Mystus sp.) exhibited the highest viable count 6.5 × 105 CFU/ml (Control), while Darikana (Esomus danricus), Chela (Salmostoma phulo), Moa (Amblypharyngodon mola), and Guchi (Mastacembelus pancalus) fish showed the lowest count (3.0 × 10² CFU/ml) at a Tetracycline concentration of 64 µg/ml. Moreover, microbial analysis using 16S rRNA gene sequencing identified twelve unique bacteria belong to genera. The most prevalent genus appears to be Enterobacter, identified by 6 strains. These include Enterobacter hormaechei strains UCHE20, RB13, AUH-ENM30 and 20710, Enterobacter ludwigii strain JCR-38 and Enterobacter sp. M3. Other identified genera included Klebsiella (with Klebsiella variicola and Klebsiella pneumoniae), Proteus (Proteus mirabilis), Macrococcus (Macrococcus caseolyticus), Acinetobacter (Acinetobacter johnsonii), and Bacillus (Bacillus sp.). This study provides valuable insights into the complex microbial dynamics in dried fish, emphasizing the need for enhanced food safety and public health measures. J. Bio-Sci. 32(2): 61-69, 2024